2020
DOI: 10.31616/asj.2020.0087
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Mid-Range Dynamic Instability in Lumbar Degenerative Spondylolisthesis

Abstract: Study Design: Retrospective evaluation.Purpose: To determine the prevalence of mid-range dynamic instability in patients with degenerative spondylolisthesis (DS) and to evaluate the clinical implication of mid-range instability (MI).Overview of Literature: Instability is identified by measuring vertebral body anterior–posterior translation on static end-range flexion and extension lateral radiographs. Mid-range kinematics could evince occult dynamic instability in which motion is not appreciated at the termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Overall, an estimated 11% of new patients had dynamic spondylolisthesis detected on standing-supine radiograph pairs alone, which may underestimate the true percentage of patients with dynamic spondylolisthesis. Other studies have reported that the percentage of patients with dynamic spondylolisthesis assessed with flexion-extension radiographs is between 10% and 25% among patients known to have degenerative spondylolisthesis [13, 19]. The estimated percentage of patients with dynamic spondylolisthesis in our study seems reasonable, given that our study used standing-supine radiographs and included patients without spondylolisthesis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Overall, an estimated 11% of new patients had dynamic spondylolisthesis detected on standing-supine radiograph pairs alone, which may underestimate the true percentage of patients with dynamic spondylolisthesis. Other studies have reported that the percentage of patients with dynamic spondylolisthesis assessed with flexion-extension radiographs is between 10% and 25% among patients known to have degenerative spondylolisthesis [13, 19]. The estimated percentage of patients with dynamic spondylolisthesis in our study seems reasonable, given that our study used standing-supine radiographs and included patients without spondylolisthesis.…”
Section: Discussionmentioning
confidence: 62%
“…However, patients without known spondylolisthesis may still have anterolisthesis, and radiographic views may differ in detecting the presence and magnitude of listhesis in these patients. Similarly, studies that have aimed to determine the prevalence of dynamic spondylolisthesis have examined patients with known spondylolisthesis and have estimated the prevalence to be between 10% [19] and 25% [13]. Thus, these prevalence estimates may not represent patients with back and leg pain, and differences in detecting the presence and magnitude of listhesis have not been examined with the use of standing and supine radiographs among patients without spondylolisthesis.…”
Section: Introductionmentioning
confidence: 99%
“…End range vs mid-range controversy Numerous studies may support the hypothesis that the range of motion between vertebrae measured from conventional exion and extension X-rays is not as valuable as analysis of the pattern of motion between the endranges of the exion-extension cycle. (109,111,132,(151)(152)(153)(154)(155)(156)(157)(158)(159) These studies support that the greatest intervertebral rotation and translation can occur as the patient moves from exion to extension and not at the end-range of intervertebral motion. These studies also document that irregularities and discontinuities in intervertebral motion can occur during the exion-extension cycle that cannot be detected from a two-frame exion-extension study.…”
Section: Choice Of Data Used To De Ne Normalmentioning
confidence: 74%
“…With upright standing exion-extension radiographs, it is known that more patient effort leads to more intervertebral motion -this is a fairly simple and intuitive concept. (68,69,111,112) Unfortunately, achieving maximum patient effort is not a simple task. For starters, it may be argued that symptomatic patients cannot be expected to exert much effort because it is painful or uncomfortable.…”
Section: Flexion-extensionmentioning
confidence: 99%
“…Some provocative tests, such as the walking, fall-related, and handgrip strength tests, can also be employed to assess the current and postoperative status of patients with LSS [25][26][27][28][29][30]. The Oswestry Disability Index score and the intensity of the patients' leg discomfort were likewise connected to the neuropathic pain component [31].…”
Section: Clinical Evaluationmentioning
confidence: 99%